Optimal conditions of Electrostatic Spray Deposition (ESD) for composite biomaterials coating for biomedical applications - Wasawat Nakkiew (2018)
Various types of metals and alloys are used for medical implants due to their excellent mechanical properties and corrosion resistance; however, their lacks of osteoinductive properties bring about the introduction of biomaterials which can help enhancing the bioactivity between the bones and the implants. Hydroxyapatite (Ca10(PO4)6(OH)2, or HA) which is one of the calcium phosphates that has similar mineral constituents of human bone, has been used as coating material to the metals/alloys substrate. Coating HA usually involves high-temperature such as the plasma spraying coating, which can alter the crystal structure of the HA partially become amorphous. The amorphous nature of HA lessen the benefits of coating with the biomaterial HA. Electrostatic spray deposition (ESD) was used in this research due to the fact that this process is simple, economical, and room-temperature operated. The preliminary results showed a promising thickness layer of about 40 μm; however, the adhesion of the coated layer to the stainless steel 316L was improved by mixing the HA powder with phosphate bioglass and cured in the vacuum furnace at 700°C. Taguchi experimental design technique was used for screening several ESD process parameters: powder feed rate, voltage, current, air volume, distances, time, and nozzle types to significant factors to the coated thickness of the ESD process. The results showed that feed rate, air volume, and time were the significant factors and then Full factorial analysis and response surface method was used for obtaining optimal conditions for the coating, as well as the predicted equation for determine the thickness coated layer with significant factors. © (2013) Trans Tech Publications, Switzerland.